New flexible sensor for the internet of things - Jing WU; Sheng LI; Jing ZHANG; Ming XIN; Ruowen TAO; Zhou ZHOU; Lijia PAN; Yi SHI (物联网学报)
The new flexible sensing technology integrates electronic information, material chemistry, biomedical engineering and nano-processing, to provide intelligent sensing terminals for the internet of things, which will be widely used in health monitoring, smart home, smart manufacturing and other fields.For the development of new materials and research on novel mechanisms, flexible sensors have gained much progress in basic parameters, such as sensitivity, response range, response time, linearity, hysteresis, and stability.The flexible sensing technology is not only limited to materials and devices, but also expands from a single device to system-level integrations.Aimed at the hot research issues in recent years, the development of new flexible sensors was introduced from four aspects: multimode integrated sensors, bionic electronic sensors, wireless signal transmission and energy supply, and intelligent information processing.